Studi Kebijakan Publik Evaluasi Alokasi Dana Desa (ADD) di Kabupaten Kendal Selama Tahun 2008-2012 - Septiyanto, Budi; Utomo, Susilo; ., Sulistyowati (Journal of Politic and Government Studies, 2013)
Regional autonomy policy authorizes the village to organize and manage administrationindependently. The authorization covers the provision of funds from the central fund balance andarea called the ADD funds in order to improve governance in the village. This research focusedto look on the achievement of results and upon exercise of ADD policy outputs in Kendal duringthe five-year period from 2008 through 2012.The methodology used in this research is descriptive method of analysis that seeks to illustratethe implementation of the ADD policies in Kendal through supporting factors and inhibiting andalso achievement in implementation. On the basis of the facts and the data field are shown toillustrate in detail and clear through the study of six evaluation criteria of effectiveness,efficiency, adequacy, equity, responsiveness and accuracy of the results obtained from in-depthinterviews with key informants.From the results obtained it turns out from year to year progress of up and down according toexperience level though disbursement activities in the village has increased in terms ofdevelopment. However, there are a number of villages that are still facing problems anddifficulties to run optimally ranging from technical issues to field problems in problematic gooduse, distribution, and usage reporting. The only perceived benefits activities that are operationaland rural development. Meanwhile empowerment activities are still lacking and far fromexpectations. ADD policy implementation in Kendal requires strategic planning and long-termactivities that can be felt by lower middle ADD’s beneficiaries.Keywords: Allocation Fund Village, Village Government, Local Government and Output.